2012
DOI: 10.1177/1358229112464450
|View full text |Cite
|
Sign up to set email alerts
|

Banning Islamic veils

Abstract: Copyright and moral rights to this thesis/research project are retained by the author and/or other copyright owners. The work is supplied on the understanding that any use for commercial gain is strictly forbidden. A copy may be downloaded for personal, non-commercial, research or study without prior permission and without charge. Any use of the thesis/research project for private study or research must be properly acknowledged with reference to the work's full bibliographic details.This thesis/research projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…As far as we are aware, no psychological research has examined how such laws and related societal narratives are perceived by Muslim youth (including girls who do and do not cover their hair) as they develop and navigate their identities. Scholars from other disciplines have argued that not only do headscarf bans create barriers to education and employment for Muslim women (Howard, 2012;Gohir, 2015;Weichselbaumer, 2016), they also reify a fictionally homogeneous Muslim outgroup, underscoring discursive boundaries between "us" and "them" (Yılmaz, 2014). Such normative boundaries undoubtedly play a role in how diverse European youth develop their identities across domains, including in the crucial context of school.…”
Section: Discrimination and Identitymentioning
confidence: 99%
“…As far as we are aware, no psychological research has examined how such laws and related societal narratives are perceived by Muslim youth (including girls who do and do not cover their hair) as they develop and navigate their identities. Scholars from other disciplines have argued that not only do headscarf bans create barriers to education and employment for Muslim women (Howard, 2012;Gohir, 2015;Weichselbaumer, 2016), they also reify a fictionally homogeneous Muslim outgroup, underscoring discursive boundaries between "us" and "them" (Yılmaz, 2014). Such normative boundaries undoubtedly play a role in how diverse European youth develop their identities across domains, including in the crucial context of school.…”
Section: Discrimination and Identitymentioning
confidence: 99%
“…Muslim women tend to have different and often multiple reasons for wearing a headscarf. Qualitative research has shown, for example, that Muslimas indicate autonomous motivations as well as reasons related to cultural traditions, religious beliefs and community expectations (e.g., Hoekstra & Verkuyten, 2015;Howard, 2012;Legate et al, 2020;Ruby, 2006;Safdar & Jassi, 2021;Wagner et al, 2012). Our focus, however, is not on the perspective of Muslimas but rather on how reasons for the wearing of the headscarf are presented in public and political debates and considered by majority group members.…”
Section: Tolerance and Perceived Reasons For Wearing A Headscarfmentioning
confidence: 99%
“…Over the past decades, many West European debates about the Muslim headscarf evolve around the question whether a secular state conflicts with Muslim women wearing a headscarf in public positions (e.g., civil servants, police officers, teachers). In these public and political debates, questions are raised about whether women wear a headscarf out of their own free choice or rather because of religious community pressures (Howard, 2012). For instance, liberals as well as some feminists have opposed the headscarf because it allegedly would symbolize gender inequality and Muslimas' lack of free choice (Everett et al, 2015;Fasel et al, 2013;Gustavsson et al, 2016;Lettinga & Saharso, 2014;Nussbaum, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What are the specific arguments in the veiling debate, and how are they related to the ideas of liberalism outlined above? Research on the political discourse on Islamic practices – especially the wearing of the veil – identifies different aspects associated with identity and immigrant integration: security concern with terrorism and political Islam, gender equality and the relation between church and state (Howard, 2012; Rosenberger & Sauer, 2012; Scott, 2007). Different arguments can be broadly distinguished (see also Nussbaum, 2012), although they are not entirely separable.…”
Section: Public Discourse Research On Anti‐muslim/islammentioning
confidence: 99%